2019
DOI: 10.3390/cells8111344
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Uteroplacental Vascular Dysfunction

Abstract: Pregnancy complications of preeclampsia and intrauterine growth restriction (IUGR) are major causes of maternal and perinatal/neonatal morbidity and mortality. Although their etiologies remain elusive, it is generally accepted that they are secondary to placental insufficiency conferred by both failure in spiral artery remodeling and uteroplacental vascular malfunction. MicroRNAs (miRNAs) are small no-coding RNA molecules that regulate gene expression at the post-transcriptional level. Increasing evidence sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 324 publications
0
15
0
1
Order By: Relevance
“…Within the context of trophoblast cell invasion, many studies have reported that various miRNAs and their target genes are associated with trophoblast cell invasion [ 12 , 46 , 47 ]. In this study, miR-675-5p promoted trophoblast cell invasion by direct suppressing GATA2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the context of trophoblast cell invasion, many studies have reported that various miRNAs and their target genes are associated with trophoblast cell invasion [ 12 , 46 , 47 ]. In this study, miR-675-5p promoted trophoblast cell invasion by direct suppressing GATA2 .…”
Section: Discussionmentioning
confidence: 99%
“…These ncRNAs can be classified into two main types: small ncRNAs (sncRNAs) with lengths of 20–50 nucleotides and long ncRNAs (lncRNAs) of >200 nucleotides [ 11 ]. Of the two types, sncRNAs, especially microRNAs (miRNAs), are also involved in the molecular mechanisms of EVT cell invasion [ 12 ]. However, little is known about the characteristic features of EVT-associated ncRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…found that lncRNA TUG1 could target miR-29b to regulate angiogenesis, invasion, apoptosis, and proliferation of trophoblast cells. In addition (Hu and Zhang, 2019), outlined how the abnormal expression of miRNAs in PE and IUGR affects trophoblast infiltration and uterine placental vascular adaptation gene expression; therefore, that article will not be described in detail.…”
Section: Placental Angiogenesismentioning
confidence: 99%
“…We have shown that the sncRNA expression profile and their potential gene targets at the morula stage reflect the efficiency of maternal‒zygotic transition and blastulation while forming embryoblasts and trophoblasts. Despite the abundance of scientific reports on the role of miRNAs in the development of IUGR and PE, summarized and discussed in Hu’s review article [ 21 ], up to date there is no information on the key experimentally proven pathogenetic participants of the “miRNA-target gene” network, which differ in IUGR and PE. In this connection, and in order to test Huppertz’s hypothesis, we compared the transcriptome and proteomic profiles in the placenta tissue from the fetal to maternal surfaces as well as in the placental bed tissue from the decidual surface to the myometrial base, containing extravillous trophoblast cells and myometrial parts of the spiral arteries, from pregnant women with PE, IUGR, and small for gestational age (SGA) newborns.…”
Section: Introductionmentioning
confidence: 99%